Balloon Modelling Step-bystep instructions to create amazing balloon models (Sufflok, UK Top That! Publishing, 2013)
Step-by-step instructions for world-famous magic tricks! From predicting colours to making a wand vanish, this ultimate guide to tricks and illusions will teach you the sleight-of-hand that you need to perform show-stopping magic!
"Includes over 10 balloon models!"
Arts (Games)
1 2
Keywords: Games